Technique of definition of control bands of parametres of customisation of combine harvesters - J.A. Tsarev; S.S. Traskovski (Advanced Engineering Research)
The design procedure of control bands of parameters of customizations of the serial combine harvesters, based on statistical results of their trials is offered